Industrial clusters in biotechnology : driving forces, development processes, and management practices - Chiesa, Vittorio (Imperial College Press ; Distributed by World Scientific Pub., 2005)
Annotation - the preconditions for a cluster to grow (scientific base and/or industrial base, innovative financing, etc.); - the driving forces for cluster growth and development, i.e. the key factors of development (new company creation, IP rules, acceptance of biotech products, services and infrastructures, etc.); - best practices in cluster management (barrier removal, network creation, marketing, technology transfer, etc.).